Modern Practice of ʽManual Managementʽ in Russian Governmental and Municipal Authority - SHLYCHKOV, Valeriy; KIYAMOV, Ilgam; KULISH, Sergey; NESTULAEVA, Diana; ALAFUZOV, Igor (Journal of Advanced Research in Law and Economics, 2018)
Objectives: to define content and structure of ʽmanual managementʽ term; to analyze motives, legal framework, legitimacy, forms and methods of using ʽmanual proceduresʽ in the management processes in entities of governmental and municipal authority in the Russian Federation; to explore foreign experience in terms of ʽmanual managementʽ; to define ratios between ʽsystemʽ and ʽmanualʽ methods in Russian management practice and to evaluate the degree of their influence on social and economic life of modern Russian society. The methodological base of the research is comprised with methods and scientific cognition techniques widely used in research practice, namely: methods of deduction and induction, generalization, observation, forecasting, scientific abstraction techniques, system analysis, as well as classification and grouping instruments, elements of cross-industry and comparative historical analysis; expert estimations. Results of the research: authors have formulated own definition of ʽmanual managementʽ term; revealed reasons, conditions and motives for its applying by Russian bodies of governmental and municipal authority; described the most spread methods of its application and factors concerning increase of cases of refuse to use system procedures in modern practice of governmental and municipal management. Scientific novelty: considering the practice of Russian governmental and municipal management authors focus on the lately applied procedures of its exercising, such as creation of parallel management structures, transition to instruments of directive instructions, etc. On the basis of conducted analysis of activity performed by bodies of governmental and municipal authority in constituent of the Russian Federation authors have revealed ratio between ʽmanualʽ and ʽsystemʽ procedures used in management process, formulated definition of ʽmanual managementʽ term, disclosed conditions and motives for its application and also made a conclusion stating the main reasons for applying and extending ʽmanual managementʽ practice are the incompleteness and inconsistency of applicable Russian legislation, which on the one hand cannot reflect to the full extent the fundamental changes in social and economic spheres that took place in Russia within the recent decades, and on the other hand is far not always able to sufficiently regulate relationships between object and subject in the process of governmental and municipal management. Practical relevance : as a result of the research authors forecast the probable consequences of outlined tendency for extension of practice of ʽmanual managementʽ in bodies of governmental and municipal authority in both - in the medium and the longer term.